GIANT ANGIOMYOLIPOMA OF KIDNEY MIMICKING RENAL CELL CARCINOMA: A CASE REPORT - *MELLONIE.P; HEMALATHA GANAPATHY; SUBHASHREE A.R (International Journal of Pharma and Bio Sciences, 2014)
Angiomyolipoma an uncommon benign neoplasm of the kidney is a triphasic tumour composed of angiomatous, smooth muscle and adipose tissue elements. They are usually associated with Tuberous sclerosis and commonly bilateral in presentation .Angiomyolipoma is often asymptomatic and is dedected incidentally in radiological studies and during autopsies. We present a rare case of a giant renal angiomyolipoma which presented with acute abdominal pain and mimicked renal cell carcinoma on imaging studies, thus creating a diagnostic challenge